PITX1 plays essential functions in cancer - Zhao, Jingpu; Xu, Yongfeng (Frontiers in Oncology, 2023)
PITX1, also known as the pituitary homeobox 1 gene, has emerged as a key regulator in animal growth and development, attracting significant research attention. Recent investigations have revealed the implication of dysregulated PITX1 expression in tumorigenesis, highlighting its involvement in cancer development. Notably, PITX1 interacts with p53 and exerts control over crucial cellular processes including cell cycle progression, apoptosis, and chemotherapy resistance. Its influence extends to various tumors, such as esophageal, colorectal, gastric, and liver cancer, contributing to tumor progression and metastasis. Despite its significance, a comprehensive review examining PITX1's role in oncology remains lacking. This review aims to address this gap by providing a comprehensive overview of PITX1 in different cancer types, with a particular focus on its clinicopathological significance.